Nurses' attitudes facing the family involvment in caring for people with mental disorder - Maria do Perpétuo Socorro de Sousa Nóbrega; Carla Sílvia Neves da Nova Fernandes; Sonia Regina Zerbetto; Francisco Miguel Correia Sampaio; Estela Duarte; Suellen Cristina da Silva Chaves; Wanderson Carneiro Moreira
ABSTRACT Objective: To characterize the attitudes of Primary Health Care nurses, regarding the involvement of the family in the care for people with Mental Disorder. Methods: Correlational study with 257 nurses from the city of São Paulo. The scale "Importance of Families in Nursing Care- Nurses' Attitudes" was used. For the analysis, descriptive and inferential statistics were used. Results: The scale scores were high, with a mean value of 82.1 (SD=8.4) favorable to the families' involvement, and are related to being a nurse in the Family Health Strategy (p<0.001), having received education/training in family nursing (p<0.005), the workload of 40 hours/week (p<0.005), working in the West, East and Center Regions (p<0.005). Conclusion: Most nurses have positive attitudes towards the involvement of families, a relevant indicator for their inclusion in the health-mental care process.